Circulating β1 Adrenergic Autoantibodies from Patients with Chronic Periodontitis Interact with Gingival Fibroblasts - Sterin-Borda, Leonor; Furlan, César; Borda, Enri (European Journal of Dentistry, 2009)
Objectives: To demonstrate the presence of circulating autoantibodies (Abs) from patients with chronic periodontitis (CP) that interacted with human gingival fibroblast membranes activating β1 adrenoceptors (β1-AR).Methods: Sera and purified IgG from 25 patients with CP and 20 age-matched healthy subjects were studied by flow cytometry, ELISA and DNA synthesis. Human gingival fibroblast membranes and/or synthetic peptides with amino acid sequences identical to human β1-AR were used as antigens.Results: By flow cytometry and ELISA procedures, we proved that the serum-purified IgG fraction from patients with CP reacted with the fibroblast surface and to the β1 synthetic peptide. The corresponding affinity-purified anti-β1 peptide Abs displayed agonist-like activity associated with specific receptor activation, inhibiting the DNA synthesis of human gingival fibroblasts.Conclusions: This study demonstrates that β1-AR autoantibodies are elevated in patients with CP. These autoantibodies were targeted to the fibroblasts, and specifically to the β1-AR, and has receptor-like activity inhibiting DNA synthesis. (Eur J Dent 2009;3:191-199)
Keywords: Cell proliferation; Cytokines; Autoantibodies; Antigens/peptides; Signal transduction; Gingival fibroblasts